The Impact Of Empathy And Social Cognition On Mental Resilience And Team Adaptation In Internal Affairs Officers (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the socio-psychological relationship between mental resilience and emotional intelligence among law enforcement officers. The results of the empirical study reveal a significant positive correlation between emotional intelligence and mental resilience. The findings highlight the importance of developing emotional intelligence as a key resource for enhancing stress resistance and professional effectiveness of law enforcement personnel.